Transformations of Difference Equations I - Sonja Currie; Anne D. Love (Advances in Difference Equations, 2010)
We consider a general weighted second-order difference equation. Two transformations are studied which transform the given equation into another weighted second order difference equation of the same type, these are based on the Crum transformation. We also show how Dirichlet and non-Dirichlet boundary conditions transform as well as how the spectra and norming constants are affected.